Optical detection of electron-nuclear double resonance for a donor in oxygen-doped GaP - DONEGAN, JOHN (My University, 1989)
Optical detection of electron-nuclear double resonance (ODENDOR) has been used in a study of an optically detected magnetic resonance spectrum previously assigned to the shallow effective-mass-like 1S(E) state of the substitutional oxygen donor in GaP. The ODENDOR spectra were observed via photoluminescence transitions which are known to be oxygen related. Hyperfine interactions with several shells of both P and Ga neighbors were observed showing that the defect center is on the P sublattice and has full Td (tetrahedral) symmetry. A substantial hyperfine interaction was observed on the Ga sublattice inconsistent with an effective-mass-like state made up from the lowest X1 conduction-band valleys. Further, the full tetrahedral symmetry of the defect as deduced from the ODENDOR spectra reveals an A1 state not consistent with the 1S(E) state believed to be involved in the electron-capture luminescence transition. Analysis of the defect wave-function distribution gives a binding energy of about 0.22 eV.
PUBLISHED
Keywords: Physics